KEJADIAN IKUTAN NEUROLOGIS PADA TENAGA KESEHATAN RUMAH SAKIT RUJUKAN COVID-19 PASCA VAKSINASI MRNA-1273 BOOSTER - Rakhmad Hidayat; Muhammad Hafiz Aini; Zlatikha Djuliannisaa; Alyssa Putri Mustika; Mohammad Kurniawan; Taufik Mesiano; Al rasyid; Salim Harris (NEURONA, 2021)
Introduction: Vaccine effectivity to decrease COVID-19 transmission has been proven by the decrease in hospitality rate and death rate caused by COVID-19. Nowadays, Indonesian health workers are fully vaccinated for more than six months. The government want to give mRNA-1273 (Moderna) vaccine as the third vaccine dose booster for health workers. The booster’s effect remains unknown, but there are some vaccine side effects. Aim: To know the neurological side effects of the Moderna vaccine that are still unknown and not yet studied in Indonesia. Methods: This study used a prospective cohort with the primary data collected through an online form filled by health workers of Universitas Indonesia Hospital that get Moderna vaccine as a booster. Research data analysis will be carried out through a comparative study through the chi-square method using SPSS 20. Results: The previous history of adverse events following immunization (AEFI) significantly affects the type, the severity degree, and the acceptance of AEFI after the Moderna vaccine booster. BMI and regular medication affect the severity degree of AEFI (P<0.05). Regular medication insignificantly increases the possibility of no side effects. Meanwhile, the use of antipyretic medication for AEFI in????uenced the history of previous AEFI (P<0.05). Discussion: AEFI is any untoward medical occurrence that follows immunisation and does not necessarily have a causal relationship with the usage of the vaccine. Further investigation is necessary to evaluate the correlation between those factors and the AEFI of the Moderna booster vaccine. Keywords: COVID-19, health workers, Moderna vaccine, vaccine side effects